2021
DOI: 10.3389/fpsyg.2021.637776
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Digital Learning During COVID-19: Competence Beliefs, Intrinsic Value, Learning Engagement, and Perceived Teacher Support

Abstract: The spread of the COVID-19 pandemic quickly necessitated digital learning, which bore challenges for all pupils but especially for groups disadvantaged in a virtual classroom. As some studies indicate persistent differences between boys and girls in use of technologies and related skills, the aim of this study was to investigate gender differences in the digital learning environment students faced in spring 2020. Previous studies investigating gender differences in digital learning largely used biological sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 93 publications
7
58
0
3
Order By: Relevance
“…With respect to gender differences, female students were found to show higher learning engagement and to receive more support from teachers than male students (Korlat et al, 2021). This finding correlates with results from previous studies, which indicate that, in general, girls are more proficient at self-regulated learning than boys (Perry et al, 2018).…”
Section: Previous Findings On Differences In Coping With Self-regulated Distance Learningsupporting
confidence: 85%
“…With respect to gender differences, female students were found to show higher learning engagement and to receive more support from teachers than male students (Korlat et al, 2021). This finding correlates with results from previous studies, which indicate that, in general, girls are more proficient at self-regulated learning than boys (Perry et al, 2018).…”
Section: Previous Findings On Differences In Coping With Self-regulated Distance Learningsupporting
confidence: 85%
“…This result could also be attributed to the fact that females tend to have a higher motivation for learning and 5 BioMed Research International breaking the cycle of possible gender inequalities. Another study also concluded that learning engagement was higher in females than in males [57]. Moreover, the present study findings revealed that the educational intervention was significantly more effective among the circulating nurses with Bachelor's degrees in comparison to those with Associate degrees.…”
Section: Discussionsupporting
confidence: 69%
“…In addition, the structure of online learning environments has a clear influence on students’ readiness to join online study ( Mäenpää et al, 2020 ). When there is a transition from face-to-face to online learning, females might adjust their methods and be more adaptable to the new learning environment ( Korlat et al, 2021 ). Du’s (2016) study discovered that males have less tendency to structure their study environment.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, Song and Li (2020) indicated that females do better than males at seeking help online when they are supported by such online tools as search engines, emails, or question and answer forums. Females are also more likely than boys to reach out to their teachers during the COVID-19 lockdown and to develop better relationships with their teachers ( Korlat et al, 2021 ). Learning relies heavily on interaction between students and teachers ( Taylor et al, 2007 ), especially in the context of an epidemic.…”
Section: Discussionmentioning
confidence: 99%